Analysis of the Implementation of Service Level Agreement (SLA) in the Process of the Realization of Sharia IB KPR Financing at PT Bank Sumut KCP Syariah HM Joni - Nina Iftiani (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
In the world of banking which is engaged in services, it is very necessary to have a Service Level Agreement. A service level agreement or what is known as a service level agreement is an agreement with guarantees for the services provided by the Bank to customers as a manifestation of responsibility for the services provided in the event of negligence or human error. The purpose of this study was to discuss the application of SLA (Service Level Agreement) at Bank Sumut KCP Syariah HM. Joni. This is done to determine the implementation of the Service Level Agreement (SLA) in the customer financing disbursement process. Is the implementation in accordance with the established Service Level Agreement (SLA) service standards. This study uses a qualitative descriptive method with interview techniques. From this research, it can be concluded that the implementation of the Service Level Agreement (SLA) in the customer financing disbursement process is not in accordance with the SLA standard due to several factors which cause the customer financing disbursement process to take longer.